Dynamic Driving Forces of India's Emissions From Production and Consumption Perspectives. Issue 8 (5th August 2020) - Wang, Zhenyu; Meng, Jing; Guan, Dabo
Abstract: While India becomes one of the largest carbon emitters in the world with a high emission growth rate, existing studies fail to capture the recent trends and the key driving factors behind it. Here, by using multiregional input‐output analysis and structural decomposition analysis, we measure the contribution of factors to the changes of India's domestic consumption and trade‐related emissions. This study finds that India's per capita consumption has a significant raising effect on India's consumption‐based emissions during 2000–2014; increasing coal proportion (especially in industry and electricity) and ineffective energy efficiency (especially in electricity) continuously push India's production‐based emissions upwards after 2003. Meanwhile, India's domestic industrial chain shows increasing and decreasing effects on domestic consumption and export‐related emissions after 2011, respectively. India's forward industrial chain always drives export‐related emissions upwards. In addition, the major contributor of final demand in domestic consumption emissions transfers from capital investment to household consumption after 2008, while the increasing power of services in export‐related emissions rapidly fades in the same period. India's climbing import‐related emissions embodied in final products shift to light industries, and the intermediate products shift to heavy industries and constructions over time. Key Points: Increasing coal proportion and energy intensity push India's emissions upwards after 2003 India's domestic industrial chain has opposing effects on domestic and trade‐related emissions after 2011, as well as demand structure India's biggest final demand shifts from capital investment to household consumption after 2008